Improving electric power generation of a standalone wave energy converter via optimal electric load control. (15th November 2020) - Wang, LiGuo; Lin, MaoFeng; Tedeschi, Elisabetta; Engström, Jens; Isberg, Jan
Abstract: This paper aims to investigate electric dynamics and improve electric power generation of an isolated wave energy converter that uses a linear permanent magnet generator as the power take-off system, excited by regular or irregular waves. This is of significant concern when considering actual operating conditions of an offshore wave energy converter, where the device will encounter different sea states and its electric load needs to be tuned on a sea-state-to-sea-state basis. To that end, a fully coupled fluid-mechanical-electric-magnetic-electronic mathematical model and an optimization routine are developed. This proposed time-domain wave-to-wire model is used to simulate the hydrodynamic and electric response of a wave energy converter connected to specific electric loads and also used in an optimization routine that searches optimal resistive load value for a wave energy converter under specific sea states. Sample results are presented for a point-absorber type wave energy converter, showing that the electric power generation of a device under irregular waves can be significantly improved. Highlights: A wave-to-wire model is developed for a point-absorber type wave energy converter (PAWEC). A new optimization procedure that identifies optimal electric load is proposed. Hydrodynamic and electric performance of a wave energy converter under random sea states are investigated.